TEACHERS’ COMPETENCY IN INCLUSIVE SCHOOLS TO PROVIDE EDUCATION FOR CHILDREN WITH DISABILITIES - Dr Mohanasundaram, P.Kamaraj (International Journal of Advanced Science and Technology, 2020)
United Nation sets the goal of Education for all including children with disabilities. According to Census 2011 report, there are 2.8 crore persons with disabilities identified in India with the categories of persons with visual, hearing, speech, loco-motor, Intellectual and Multiple disabilities. The United Nation’s Convention on the Rights of Persons with Disabilities 2006 (UNCRPD), enforced to provide the Education as the Rights of Children with disabilities. Sarva Shiksha Abhiyan (SSA) Rashtria Madhyamik Sikhsha Abhiyan(RMSA) and Samakra Sikhsha Abhiyan clearly states that every child with special needs, irrespective of category and degree of disability, is provided education in an appropriate environment. The competency of teachers is an important factor to implement inclusive education program for children with disabilities in the class room. This study involved the school teachers across the level to understand the competency of teachers for    providing inclusive education to the children with disabilities. As part of the study the competency of teachers on identification and management of children with multiple disabilities conducted through survey using a tool developed for the purpose is conducted. The result reveals that there is no significant difference in the competency of teachers working across the level to provide inclusive education for the children with multiple disabilities across the level. However the competency of the teachers working across the level to provide inclusive education for children with disabilities found to be near 30% and the teachers working across the level in inclusive education program needs training program to gain rest of the skill and competencies to provide inclusive education for the children with multiple disabilities.